The early function of cortisol in liver during Aeromonas hydrophila infection: Dynamics of the transcriptome and accessible chromatin landscapes - Jiang, Hucheng; Sun, Mengling; Zhao, Yanhua; Liu, Guoxing; Zhong, Liqiang; Xue, Hui; Chen, Xiaohui; Zheng, You; Wang, Minghua (Frontiers in Immunology, 2022)
In China, the channel catfish (Ictalurus punctatus) is an important aquaculture species; however, haemorrhagic disease (Aeromonas sp. induced disease) in these fish has caused tremendous economic loss due to high morbidity and mass mortality in the breeding industry. The role of cortisol in bacterial diseases, particularly in the acute phase, remains unclear. In this study, liver transcriptome (RNA-seq) and chromatin accessibility (ATAC-seq) analyses were employed to investigate the early functional role of cortisol in Aeromonas hydrophila-stimulated responses. Our experiments confirmed that A. hydrophila infection can initially significantly increase serum cortisol levels at 1 h after infection. At this time point, the increased serum cortisol levels can significantly regulate A. hydrophila-regulated genes by affecting both transcriptome and chromatin accessibility. Cross-analysis of RNA-seq and ATAC-seq revealed that a certain gene group (92 target_DEGs) was regulated at an early time point by cortisol. KEGG enrichment analysis revealed that the top three pathways according to target_DEGs were cancer, glutathione metabolism, and the Notch signalling pathway. The protein-protein interaction analysis of target_DEGs revealed that they may be primarily involved in cell proliferation, CD8+ T cell function, glutathione synthesis, and activation of the NF-κB signalling pathway. This suggests that after the emergence of immune stress, the early regulation of cortisol is positive against the immune response. It is possible that in this situation, the animal is attempting to avoid dangerous situations and risks and then cope with the imbalance produced by the stressor to ultimately restore homeostasis. Our results will contribute to future research on fish and provide valuable insight regarding the mechanism of immune regulation by cortisol and the study of bacterial haemorrhagic disease in channel catfish.